Transparency Mode of Hearable Reduces Your Spatial Hearing: Evaluation and Cancelling Method to Restore Spatial Hearing - Hiroki Watanabe; Tsutomu Terada (IEEE Access, 2023)
Many earphone-type wearable devices (hearables) with noise-canceling features can capture external sound and present it to the user (transparency mode). This function helps the user avoid being cut off from the outside while wearing the earphones. However, because the built-in microphone/speaker has a frequency response, the presented sound differs from the sound acquired by the user’s original auditory system. Since humans use a head-related transfer function (HRTF) to identify the direction of sound sources, changes in the user’s HRTF caused by transparency mode may adversely affect their sound localization ability. Therefore, this study investigated the changes in sound localization ability when using the transparency mode of commercially available hearables. A sound localization experiment was conducted on 10 participants using three hearables to identify 12 sound sources separated by 30° around each participant. The results show that the accuracy of sound localization decreases from 91.5% to 68.9% when using transparency mode. Moreover, a method was proposed to cancel the device’s microphone/speaker frequency characteristics. Evaluation results confirmed that the proposed method increased the accuracy of sound localization from 62.7% to 72.0%.